2015
DOI: 10.1001/jamapediatrics.2015.2186
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Metformin Use on Height in Children and Adolescents

Abstract: IMPORTANCE Metformin hydrochloride use is increasing in children and adolescents. Previous meta-analyses have identified a large variability in the effects of metformin use on body mass index changes but have not considered height changes as a confounder, to our knowledge.OBJECTIVE To conduct a systematic review and meta-analysis of the effects of metformin use on height in children and adolescents.DATA SOURCES Computerized databases, including MEDLINE and EMBASE, were searched up to September 9, 2014, for ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…We found 3 or 30 mg/ kg/day for 7-days pretreatment were not effective. Similarly, recent study suggested that the biological effects of metformin may be attributable to its cumulative dosage based on the dosage administrated daily [15,16]. Therefore, it seems the cumulative metformin dosage may closely relate with its neuroprotection against ischemic brain injury.…”
Section: Figmentioning
confidence: 96%
“…We found 3 or 30 mg/ kg/day for 7-days pretreatment were not effective. Similarly, recent study suggested that the biological effects of metformin may be attributable to its cumulative dosage based on the dosage administrated daily [15,16]. Therefore, it seems the cumulative metformin dosage may closely relate with its neuroprotection against ischemic brain injury.…”
Section: Figmentioning
confidence: 96%
“…Plus, one significant meta-analysis concluded that the administration of metformin in children and adolescents resulted in a dose–response relationship between metformin use and increases in height in those populations compared with controls. While an approximate 1-cm increase in height may appear small, it seemed likely underestimated given that many studies were of short duration and included older adolescents, potentially after epiphyseal growth plate closure [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitiligo melanocytes produce insulin-like growth factorbinding protein (IGFBP) 3 [38], the expression of which is, like IGF-1, growth hormonedependent [39]. In addition, metformin, which regulates IGF level, has been shown to modulate height [40], inhibit tumor growth [41,42], and lower the risk of incident vitiligo [43]. This connects vitiligo to height and cancer incidence (which is known to be related to tall stature) [44].…”
Section: Discussionmentioning
confidence: 99%